Analysis Of The Effectiveness Of Using Learning Media During The Covid-19 Period With The Multi-Attribute Utility Theory - Irfan Faruqi, Nouval; Maita, Idria; Ahsyar, Tengku Khairil; Fronita, Mona (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Learning activities during the Covid-19 pandemic were carried out online with the aim of taking advantage of technological advances using online learning media. All high schools have implemented online learning, one of which is SMAN 1 Bukit Batu. This aims to ensure that the learning process is carried out remotely without having to meet in person. Online learning has advantages and disadvantages that can affect the achievement of learning objectives, especially in theoretical and practical PKOK subjects. So it is necessary to assess learning theory and practice of PJOK to determine the effectiveness of both. Research the use of 6 criteria and compare theoretical and practical PJOK learning models to determine the best model. The method used is Multi-Attribute Utility Theory (MAUT) with a quantitative approach where data collection is carried out through surveys. There were 193 respondents, namely all 12th grade students of SMAN 1 Bukit Batu as the population in this study. The results of calculations using the MAUT method on the effectiveness of using online learning media during the Covid-19 pandemic resulted in the choice of the Theory subject assessment (0) as the lowest assessment, while the Practice subject (0.32) was the highest assessment. This assessment states that online learning can be said to be effective for practical subjects, while theoretical subjects are more effective if done offline